GANGGUAN PERKEMBANGAN INTELEKTUAL: TINJAUAN METODE IDENTIFIKASI DAN PENANGANAN DI SDN DIMONG 03 MADIUN - Mutin Kartika Dewi; Mochamad Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to identify intellectual development disorders (IDPs) along with management strategies for children with special needs in elementary schools and to describe the implementation of appropriate education for them. The background of the problem includes the urgent need to provide significant educational services for children with physical and mental disabilities, as well as the importance of community and government understanding of the rights of children with special needs. The method used in this study is a qualitative descriptive approach, involving observation, interviews with teachers and parents, and document analysis related to student development at SDN Dimong 03. The results of the study indicate that children with IDPs require a more individual, interactive, and practical skills-based educational approach, because verbal or abstract learning methods are often ineffective. This study emphasizes the importance of ongoing support to help children with special needs overcome academic challenges and achieve independence.